Large Eddy Simulation of a Vortex Ring Impacting a Bump (Advances in Applied Mathematics and Mechanics, 2014)
A vortex ring impacting a three-dimensional bump is studiedusing large eddy simulation for a Reynolds number Re=$4$x$10^4$ based on the initial diameter andtranslational speed of the vortex ring. The effects of bumpheight and vortex core thickness for thin and thick vortexrings on the vortical flow phenomena and the underlyingphysical mechanisms are investigated. Based on the analysis ofthe evolution of vortical structures, two typical kinds ofvortical structures, i.e., the wrapping vortices and thehair-pin vortices, are identified and play an important role inthe flow state evolution. The boundary vorticity flux isanalyzed to reveal the mechanism of the vorticity generation onthe bump surface. The circulation of the primary vortex ringreasonably elucidates some typical phases of flow evolution.Further, the analysis of turbulent kinetic energy reveals thetransition from laminar to turbulent state. The resultsobtained in this study provide physical insight into theunderstanding of the mechanisms relevant to the flow evolutionand the flow transition to turbulent state.